2019
DOI: 10.21203/rs.2.19608/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Prevalence and Risk Factors of Post-Partum Haemorrhage in Africa: A systematic review.

Abstract: Background Postpartum Haemorrhage is the loss of blood that is 500 ml or greater than 500ml following a vaginal delivery or blood loss that is more than or equivalent to 1000 ml post-caesarean section. Post-partum Haemorrhage is the leading cause of maternal mortality, and to our knowledge, there is less evidence of a systematic review being published on the prevalence and associated risk factors of PPH in Africa. Additionally, findings from previous studies about the prevalence and risk factors of PPH in Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…The prevalence of obstetric blood loss varies significantly with the setting of the study; for example, 9.0%, 9.4%, and 16.6% in Uganda, Sidama regional state, and southern Ethiopia, respectively [7][8][9]. A systematic review study in Africa showed a prevalence rate of 3.51% [10]. Apart from the known causes of obstetric blood loss post-delivery, studies have reported such factors as maternal age, antepartum anemia, abnormal labor, history of obstetric hemorrhage post-delivery in the previous pregnancies, and instrumental deliveries, multiparity, prolonged labor, CS delivery, multiple pregnancy, and big baby, to contribute significantly to its occurrence [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of obstetric blood loss varies significantly with the setting of the study; for example, 9.0%, 9.4%, and 16.6% in Uganda, Sidama regional state, and southern Ethiopia, respectively [7][8][9]. A systematic review study in Africa showed a prevalence rate of 3.51% [10]. Apart from the known causes of obstetric blood loss post-delivery, studies have reported such factors as maternal age, antepartum anemia, abnormal labor, history of obstetric hemorrhage post-delivery in the previous pregnancies, and instrumental deliveries, multiparity, prolonged labor, CS delivery, multiple pregnancy, and big baby, to contribute significantly to its occurrence [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Other risk factors include obesity, fever during pregnancy, bleeding before delivery, and heart disease. 2 A recent systemic review (2019) 6 on prevalence and risk factors of postpartum haemorrhage, found that the risk factors of PPH include: the use of assisted reproductive treatment (ART), Pregnancy Induced Hypertension, severe vaginal/perineal lacerations and macrosomia. Some scholars working in America, reported spontaneous delivery, caesarean section, forceps delivery, labour induction, non-use of oxytocin or other uterotonic agents in the third stage of labour, history of PPH, multiple pregnancies and fetal macrosomia as risk factors of PPH.…”
Section: Introductionmentioning
confidence: 99%